2018
DOI: 10.1080/14693062.2018.1454882
|View full text |Cite
|
Sign up to set email alerts
|

Key challenges for the establishment of the monitoring, reporting and verification (MRV) system in China’s national carbon emissions trading market

Abstract: An effective system for monitoring, reporting and verification (MRV) is the cornerstone of any carbon emissions trading market. This paper analyses existing MRV frameworks in China, including under the seven emission trading pilot schemes, to identify four key challenges for the establishment of an effective MRV system for China's forthcoming national carbon emissions trading market: (1) ambiguity in the legal status of relevant policies and regulations, (2) unclear requirements for the content of monitoring p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 31 publications
1
11
0
1
Order By: Relevance
“…The main carbon pricing mechanisms include price-based ones, such as carbon taxes, and quantity-based mechanisms, such as carbon trade. Scholars have compared the two mechanisms [10] and examined a dual-track model that combines both carbon taxes and carbon trade [4]. Studies on carbon trade mainly focus on the design of total allowances [11], the impact of coverage [12], the principle of allowance allocation [12], the flexible control measures [13], and quota withdrawal mechanism [14].…”
Section: Introductionmentioning
confidence: 99%
“…The main carbon pricing mechanisms include price-based ones, such as carbon taxes, and quantity-based mechanisms, such as carbon trade. Scholars have compared the two mechanisms [10] and examined a dual-track model that combines both carbon taxes and carbon trade [4]. Studies on carbon trade mainly focus on the design of total allowances [11], the impact of coverage [12], the principle of allowance allocation [12], the flexible control measures [13], and quota withdrawal mechanism [14].…”
Section: Introductionmentioning
confidence: 99%
“…The seven regional ETS pilots were initiated by planning documents and rules of the NDRC [3], formerly known as the State Planning Commission. The regional pilots have been implemented by a combination of Local People's Congress (LPC) rules [3], [4] and [5], and rules of sub-national departments of the NDRC and subsequently the MEE. These sub-national rules have provided the implementation detail for the broad principles and objectives set out by the NDRC [6].…”
Section: Regional Pilot Etsmentioning
confidence: 99%
“…Since 2018, Guangdong (unlike some pilots) has required monitoring plans, set deadlines and required information, such as monitoring boundaries of the company, monitoring methods and data selection [8]. Pilot experience shows that requiring adequate monitoring plans improves data quality, and monitoring and reporting of emissions [4] and [23]. Zeng Xuelan indicated that the most important lesson from experience of monitoring plans in Guangdong is that they should not be revised in the absence of important changes to the enterprise's situation.…”
Section: Regional Pilot Etsmentioning
confidence: 99%
“…An effective MRV system is the cornerstone of the ETS. The article by Tang et al (2018) reviews the work that has been accomplished with regard to the preparation of an MRV system for China's national ETS and the implementation of relevant requirements, and identifies four key challenges in this respect: (1) ambiguity in the legal status of relevant policies and regulations in the MRV system; (2) unclear requirements for the content of the monitoring plan; (3) lack of consistency and harmonization in the accounting and reporting guidelines; and (4) insufficient usage of information technology in the MRV system. To address these challenges, it is proposed to create a framework legislation that is legally binding and of a sufficiently high legal status to facilitate legal enforcement of the MRV requirements and increase legal assurance, to establish clear rules on the content of the…”
Section: Data Challengesmentioning
confidence: 99%
“…The article by analyses the major data requirements for China's national system, the current availability and quality of the required data and corresponding challenges, and presents both short-and long-term solutions. Along a similar theme, the article by Tang et al (2018) introduces existing monitoring, reporting and verification (MRV) frameworks in China, identifies key challenges for establishing an effective MRV system for the national system and puts forward countermeasures.…”
Section: Introductionmentioning
confidence: 99%